Cylindrical inertial electrostatic confinement plasma source for surface treatment. (November 2021) - Tiedemann, Dominik; Hofmann, Patrick; Emmerlich, Jens; Chan, Yung-An; Ulrich, Sven; Herdrich, Georg; Müller, Matthias
Abstract: The inertial electrostatic confinement (IEC) has been commonly researched in the scope of application for space propulsion and fusions reactors since many years. The utilization as thruster is possible due to a free emitting stream in a so-called jet mode of the IEC source. Depending on the setup, this jet can be operated as high energetic electron beam (tight jet) with electron energies of several keV or as low energetic plasma jet close to quasineutrality (spray jet). These modes are of high interest for thin film applications and plasma treatment. However, the IEC source is still not used in this field of application. Relevant application scopes can be electron substrate heating, surface plasma pretreatment, ionized physical vapor deposition and plasma enhanced chemical vapor deposition. In this paper, a cylindrical IEC source is presented that emits the plasma in both known jet modes, spray jet and tight jet. The jet emission occurs in radial outlet direction along the entire source height ("curtain-like" emission). Furthermore, an ignition test and operational behavior test is introduced. A stable spray jet operation region was examined and dependencies on pressure and voltage are investigated.